TECHNICAL ORAL PRESENTATIONS: KNOWLEDGE AND PRACTICES AMONG TECHNICAL STUDENTS - Siti Aisyah binti Akiah; Hazila Kadir @ Shahar (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Abstract: Oral presentation is one of the challenging tasks faced by most tertiary level students. For technical students, they have no exception in delivering technical oral presentations (TOPs) at the end of each course offered according to their fields of expertise. Realising the fact that these students should have been exposed well with integral requirements of TOP, it is essential to find out the students’ knowledge and practices on this type of presentation beforehand. Thus, this paper does not only aim to explore the respondents’ overall feedback on TOP, but also to find out the respondents’ experiences in conducting TOP. A random survey was therefore conducted and 130 students of Universiti Tun Hussein Onn Malaysia, specialised in different technical fields were selected to be the participants. A questionnaire consisted of 20 items which required them to reflect on their knowledge and experiences regarding TOP were utilised to reveal results for this research. In addition, the reflections of their experiences revealed their awareness and mistakes made during their own TOP. It is hoped that these results helped to raise awareness among technical educators about the problems occurred among their students, so that suitable guidelines and best practices can be adapted into their teaching and learning process.